SAT0369 Heterogeneity in the underlining pathogenesis in patients with connective tissue disease-associated borderline mean pulmonary arterial pressure and its distinctive hemodynamic characteristics from those with normal pulmonary arterial pressure. (15th June 2017) - Yamasaki, Y; Asari, Y; Tsuchida, K; Suzuki, K; Akashi, YJ; Okazaki, T; Ozaki, S; Yamada, H
Abstract : Background: Borderline mean pulmonary artery pressure (PAP) (21–24 mmHg) may comprise a transition phase from normal pulmonary hemodynamic condition to pulmonary arterial hypertension (PAH), which is one of the fatal complications in connective tissue diseases (CTD) [1]. The accumulated evidence is not enough to conclude that treatment for PAH in this stage may be associated with improving clinical outcomes. On the other hand, CTD-associated PH is caused by various cardiopulmonary comorbidities. It is possible that borderline mean PAP, like overt PH, is caused not only by pulmonary vasculopathy but also by cardiac and pulmonary complications [2]. Objectives: To clarify whether patients with borderline mean PAP associated with CTD have distinctive hemodynamic characteristics from those with normal mean PAP and its underlining pathogenesis is heterogeneous as those with manifest PH. Methods: We retrospectively investigated 76 CTD patients who underwent right heart catheterization from 2008 through 2016. Of the 76 patients, 25 (33%) and 16 (21%) had manifest PH and borderline mean PAP, respectively. The rest of the 35 patients had normal mean PAP. Systemic sclerosis was the most common CTD among the enrolled patients (61%), followed by MCTD (16%). Hemodynamic characteristics and findings after exercise echocardiography in patients having normal mean PAP, borderline mean PAP, and PH were compared. We also determined the validity of therapeutic intervention. Results: The values of tricuspid regurgitation pressure gradient (TRPG) were comparable between patients with borderline (31.1±7.8 mmHg) and normal mean PAP (28.3±6.9 mmHg) (P=0.1572) but its value became significantly higher in patients with borderline mean PAP (39.1±8.0 mmHg) than in those with normal mean PAP (32.8±7.4 mmHg) after exercise echocardiography (P=0.0391). Pulmonary arterial wedge pressure was significantly elevated in patients with borderline mean PAP (12±3 mmHg) compared with that in normal mean PAP (7±3 mmHg) (P<0.0001) and its value was comparable to those with overt PH, suggesting the heterogeneity on the cause of borderline mean PAP among CTD patients. The clinical course of 10 patients with borderline mean PAP was studied. Five were treated for precapillary disease, 3 for postcapillary disease, and 2 for interstitial lung disease (ILD). Normalization of mean PAP was seen in 3/4 and 3/3 of the patients treated for precapillary and postcapillary disease, respectively. Deterioration of TRPG was seen in one patient after receiving pulmonary vasodilators. One with severe ILD developed PH. Conclusions: The pathogenesis of borderline mean PAP, clearly distinctive from normal mean PAP, was heterogeneous as that of manifest PH in CTD patients. Though the clinical course may be altered with appropriate therapeutic intervention, repeated assessment is needed. References: Kovacs G, Olschewski H. Borderline pulmonary pressures in scleraderma - "a pre-pulmonary arterial hypertension" condition? Arthritis Res Ther 2015; 17: 123, 015–0649–7. Kovacs G, Avian A, Tscherner M, et al. Characterization of patients with borderine pulmonary arterial pressure. Chest 2014; 146: 1486–93. Disclosure of Interest: None declared